(untitled) (Contemporary Central & East European Law, 2024)
The model of the general administrative procedure in Poland is governed by the Code of Administrative Procedure of 14 June 1960. This act has undergone numerous amendments aimed at adapting the administrative procedure to the requirements of a democratic state governed by law and providing appropriate procedural guarantees to individuals. Despite the phenomena of decodification and atomisation of the administrative procedure resulting from specific regulations, the code model of administrative procedure remains the fundamental formal and procedural framework for the jurisdictional activities of administrative bodies. Contemporary trends in modernisation are characterised by several development directions, including: pragmatisation, which involves the de-formalisation of activities towards third-generation procedures; automation, which relies on electronic data processing systems; and Europeanisation, encompassing the development of procedures integrated with European Union law. These trends lead to new institutions and legal regulations being introduced into the model of the general administrative procedure, such as simplified procedures, the tacit settlement of cases, electronic deliveries, the handling of cases using automatically generated documents and European administrative cooperation. With this in mind, the study focuses on the analysis and assessment of the impact of pragmatisation, automation and Europeanisation on code regulations governing administrative jurisdiction. It aims to formulate conclusions regarding the appropriateness of current amendments and propose recommendations for future changes.